Taxonomy of the myrmecophilous genus Lomechusa (Coleoptera: Staphylinidae: Aleocharinae: Lomechusini) from China - Chen, Yong-Jie; Zhou, Hong-Zhang (Zootaxa, 2007)
This paper studies the taxonomy of the myrmecophilous genus Lomechusa Gravenhorst, 1806 from China and describes four new species: Lomechusa elegans Chen & Zhou, n. sp. from Beijing, Lomechusa brevicornis Chen & Zhou, n. sp. from Beijing, Lomechusa seticornis Chen & Zhou, n. sp. from Hunan, and Lomechusa parva Chen & Zhou, n. sp. from Tibet. A key to all seven Chinese species of the genus Lomechusa is provided.